Respuesta inmune contra antígenos menores de histocompatibilidad en el trasplante alogénico de progenitores hematopoyéticos - Pérez N., Claudio; Rabanales T., Ramón; Larrondo L., Milton; Alfaro L., Jorge (Revista Hospital Clínico Universidad de Chile, 2010)
Patients who receive allo hematopoietic stem cell transplantation (SCT) could develop graft versus host disease and/or graft versus tumour effect. These immunological responses can happen even with perfect fully HLA matched haematopoietic stem cells. Moreover, the engraftment of the donor’s cells depends on the immunological conditions of both donor and recipient. The development of alloreactivity occurs in the context of the polymorphisms of the human genome, these genomic differences results in proteins with antigenic properties which trigger immune responses. Considering this, the SCT is a powerful tool to heal the patient disease, because all of them become chimeras. In other words, into individuals with two different genomic sets, which will develop a strong immunological response that cannot exist in natural conditions.